Peran Guru PPKn Dalam Penguatan Norma Hukum Untuk Mengatasi Perilaku Bullying Pada Siswa Kelas VII SMP NEGERI 18 Surakarta Tahun Pelajaran 2023/2024: Indonesia - Mutiasih Anisya Dewi; Supeni, Siti; Farida Sari, Ama (Prodi PPKn Universitas Slamet Riyadi, 2025)
The purpose of this research was 1) to determine the forms of bullying behavior that occurred in students in class VII of SMPN 18 Surakarta, 2) to determine the role of Civics teachers in providing reinforcement of legal norms to overcome bullying behavior at the seventh grades students of SMPN 18 Surakarta. The from of this research was qualitative reseach. The research steategy used was a case study. The subjects in this research were the deputy principal for student affairs, civics theacher in class VII, guidance and counseling teacher, and students in clasdd VII. The data sources used were primary data sources and secondary data sources. The data collection tecniques used were observation and triangulation. The data in this research was analyzed using an interactive model. The results of this research could be concluded that 1) the forms of bullying behavior that occur in class VII were verbal and physical bullyinng. Verbal bullying acts ythat often occur in class were calling friends by their parent’s names, making fun of and ridiculing them. Meanwhile, physical actions included kicking, hitting, throwing stones and choking. 2) strengthening legal norms carried out by civics teachers in class VII was by providing learning materials in accordance with the curriculum, giving advice to students not to carry out acts of bullying, and punishing perpetrators of bullying so that they felt deterred andnot to carry bullying acts again. Keywords: bullying, legal norms, role of Civics Teachers.